Bifid Anterior and Posterior Arches of Atlas: Surgical Implication and Analysis of 70 Cases. Issue 2 (7th April 2015) - Goel, Atul; Nadkarni, Trimurti; Shah, Abhidha; Ramdasi, Raghvendra; Patni, Neeraj
Abstract: BACKGROUND: On reviewing the database of patients with craniovertebral junction anomalies, the authors identified 70 patients with a bifid posterior arch of atlas. OBJECTIVE: To speculate on the pathogenesis of spondyloschisis of both the anterior and posterior arches of atlas, particularly as it relates to atlantoaxial instability. METHODS: Seventy patients with bifid anterior and posterior arches were identified by a retrospective review of the database from 2007 to 2013. RESULTS: The ages of the patients ranged from 14 months to 50 years. The patients were divided into 3 groups. Group 1 (3 patients) had multiple additional spinal bony and neural abnormalities. Group 2 (34 patients) had mobile and partially (5) or completely (29) reducible atlantoaxial dislocation. Group 3 (33 patients) had atlantoaxial instability and related basilar invagination. The os odontoideum was identified in 21 patients, and C2-3 fusion was seen in 24 patients. Two of 3 patients in group 1 were treated conservatively and without any surgery. All patients in groups 2 and 3 were surgically treated. Surgery was done using lateral mass plate/rod and screw fixation techniques. The general observation during surgery included identification of discrete movements of both halves of the atlas, lateral positioning of the facets of atlas in relation to the facets of the axis and occipital condyle and closer approximation of the occipital bone, atlas, and axis resulting in "crumpling" of bone and neural elements. CONCLUSION: Understanding of the pathogenesis and mechanical alterations in cases with a bifid arch of atlas can assist in evaluating the clinical implications and in conduct of surgery.